2021
DOI: 10.1016/j.ijscr.2021.106254
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic renal infarction after left upper lobectomy: Case report

Abstract: Background Renal infarction after pulmonary resection is relatively rare; however, it is associated with severe morbidity. Case presentation An 80-year-old woman without any severe comorbidity or smoking history underwent left upper lobectomy (LUL) concomitant with mediastinal lymph node dissection for lung adenocarcinoma. She did not show fever, flank pain, and/or nausea; however, laboratory data revealed an elevated white blood cell count (WBC) (13,460 cells/mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Since only 1% of RIs found at autopsy are diagnosed antemortem [ 7 ], many of them are overlooked, and the exact number is still unknown. In many instances, the symptoms are nonspecific and may be mistaken for those caused by renal pyelonephritis, renal colic, acute mesenteric events, or urinary tract infections, which can cause delays in diagnosis and treatment [ 5 , 6 ]. Previous studies have reported elevations in white blood cell count, LDH, C-reactive protein, and creatinine in blood investigations, as well as hematuria in urinalysis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since only 1% of RIs found at autopsy are diagnosed antemortem [ 7 ], many of them are overlooked, and the exact number is still unknown. In many instances, the symptoms are nonspecific and may be mistaken for those caused by renal pyelonephritis, renal colic, acute mesenteric events, or urinary tract infections, which can cause delays in diagnosis and treatment [ 5 , 6 ]. Previous studies have reported elevations in white blood cell count, LDH, C-reactive protein, and creatinine in blood investigations, as well as hematuria in urinalysis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A thrombus here might develop because of turbulent flow or stasis of blood in the stump [ 1 ]. There have been only 13 reports of RI after surgery for lung cancer (Table 1 ) [ 4 , 5 , 8 17 ], including our case, and they included left lung cancer with isolation of the left superior pulmonary vein. In these cases, the median time to RI onset was POD 4 (interquartile range, POD 3–12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation